The Effectiveness of Computer-Assisted Language Learning (CALL) by Smartphones to Increase English Proficiency of Papuan EFL Students - Kafryawan, Wira (Institut Agama Islam Negeri (IAIN) Curup, 2023)
This study aims to find out the effectiveness of Computer-Assisted Language Learning (CALL) by smartphones to increase English proficiency of Papuan EFL students. The mixed method was implemented specifically related to the explanatory sequential design (Quantitative-Qualitative) where the research design comprised two interactive sequential stages. The first stage was carried out by collecting and analyzing quantitative data using the pre-experimental method to find out the difference before and after being given treatment. The samples were determined using purposive sampling where 30 Papuan EFL students were selected, and data were analyzed by using SPSS. The second stage was carried out by collecting and analyzing qualitative data using structured interviews. The samples were determined using purposive sampling also, and 7 Papuan EFL students were considered representative to obtain data. The results show that Computer-Assisted Language Learning (CALL) by smartphones is effective to increase English proficiency of Papuan EFL students by a significant increase of 38.70%. The effectiveness of this learning cannot be separated from the aspects of efficiency, flexibility, and accessibility supported by excellence in terms of visualization and auditory systems. Moreover, some factors that certainly become constraints of Computer-Assisted Language Learning (CALL) including internet networks, small screens, notifications and advertisements, lack of proficiency towards applications, unsupported smartphones, and battery power. By solving all these constraints, CALL can be more effective to be applied in teaching and learning. The significant implication provides better change in the world of education through learning strategies in utilizing technology especially certain context and conditions in Papua.